2011
DOI: 10.1128/aem.02567-10
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Nodulation Interferes with Impacts of Nitrogen Fertilization Levels on the Leaf-Associated Bacterial Community in Soybeans

Abstract: The diversities leaf-associated bacteria on nonnodulated (Nod ؊ ؉؉ soybeans (46% to 76%) and, conversely, increased those of Gammaproteobacteria and Firmicutes in these mutant soybeans. In the Alphaproteobacteria, cluster analyses identified two operational taxonomic units (OTUs) (Aurantimonas sp. and Methylobacterium sp.) that were especially sensitive to nodulation phenotypes under SN fertilization and to nitrogen fertilization levels. Arbuscular mycorrhizal infection was not observed on the root tissues exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…The results and previous data (18)(19)(20) strongly suggest that the manipulation of genetic factors underlying RN and AM symbioses would have significant effects on the diversity of plant-associated microbes. To investigate the roles of such plant genes in interacting with plant-associated Alphaproteobacteria such as the Sphingomonadales, the significance of the diversity and functionality of plant-associated Alphaproteobacteria in relation to rice plant growth should be examined.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results and previous data (18)(19)(20) strongly suggest that the manipulation of genetic factors underlying RN and AM symbioses would have significant effects on the diversity of plant-associated microbes. To investigate the roles of such plant genes in interacting with plant-associated Alphaproteobacteria such as the Sphingomonadales, the significance of the diversity and functionality of plant-associated Alphaproteobacteria in relation to rice plant growth should be examined.…”
Section: Discussionsupporting
confidence: 63%
“…Since nodulation is autoregulated by signal transduction between root and shoot tissues (31), it is of interest to compare bacterial communities in shoots between wild-type and symbiosis-defective mutants. Indeed, the results of our previous study of stem-and leaf-associated bacteria suggested that a subpopulation of Proteobacteria in soybean was controlled through the system that regulates RN symbiosis (18)(19)(20).…”
mentioning
confidence: 99%
“…At the time of writing, the genus Aureimonas contained three species, Aureimonas altamirensis (the type species), Aureimonas frigidaquae and Aureimonas ureilytica (Rathsack et al, 2011). Members of Aureimonas have been also isolated from the surfaces and internal tissues of rice leaves (Mano et al, 2007) and stems of hypernodulated soybeans (Anda et al, 2011). Culture-independent studies of the leaf-associated bacterial community in soybeans have shown that the majority of the population consists of members of Aureimonas closely related to A. ureilytica (Ikeda et al, 2010a(Ikeda et al, , b, 2011.…”
mentioning
confidence: 99%
“…Several studies using metagenomic or metaproteomic approaches to the bacteria of plant leaves did not detect methanotrophs, 10,23) whereas other detected methanotrophs related to Methylosinus, Methylobacter, and Methylococcus, with findings that methanotrophs have a small population on leaves. [24][25][26] Methanotrophs were successfully cultivated from 12% of the phyllosphere samples (consisting of leaves, flowers, and bark), as against 59% of the rhizoplane samples. Thus, the leaves may be able only to sustain small populations of methanotrophs due to limited nutrients on the leaves or competition with other microorganisms.…”
mentioning
confidence: 99%